Comparison of PSA Response to Generic Versus Innovator (Zytiga) Formulations of Abiraterone in Metastatic CRPC: A Retrospective Analysis - Sharath Kumar; Amit Joshi; Apurva Takke; Diana Varghese; Shruti Pathak; Vanita Noronha; Kumar Prabhash; Vikram Gota (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Abiraterone acetate has been shown to enhance overall survival and radiographic progression-free survival (rPFS) in men with metastatic castration-resistant prostate cancer (mCRPC). Presently, multiple generic brands of abiraterone are accessible in India. Nevertheless, evidence supporting the clinical equivalence of these generics when compared to the innovator has not been established, and thus, questions regarding their quality persist.